OPTIMASI VARIASI KONSENTRASI LIPID TERHADAP KARAKTERISTIK FISIK SOLID LIPID NANOPARTICLE (SLN) GLIBENKLAMID - Nurul Arfiyanti Yusuf; Rahmad Aksa; Fisa Juniawan Cahyono (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Glibenclamide is a sulfonylurea drug compound used as oral antidiabetic. Solid Lipid Nanoparticles (SLN) are alternative carrier systems that can be used to increase the bioavailability of drugs with low solubility. The purpose of this study was to determine the effect of lipid concentration on the efficiency of Solid Lipid Nanoparticle (SLN) entrapment efficiency of glibenclamide, to determine the optimum concentration of lipids which had the best Solid Lipid Nanoparticle (SLN) efficiency parameter values ​​of glibenclamide. This study varied between glyceryl monostearate and oleic acid as a lipid phase made in 12 formulas. The method of making solid lipid nanoparticles used by the solvent emulsion / evaporation method. The results of the study showed that the concentration variations between oleic acid lipids and glyceryl monostearate had a significant effect on percent entrapment efficiency in glibenclamide Solid Lipid Nanoparticle (SLN) preparations. The optimal formula is a formula with 1% oleic acid and 9% glyceryl monostearate which has particle size of 294.6 nm with a PI value (polydispersity index) of 0.465 .